The Territorial – Administrative Delimitation of Bulgaria and its Lessons for Moldova - Sergiu Cornea (Journal of Danubian Studies and Research, 2014)
Moldova has clearly established the strategic direction of development - the European Integration. In this context, it requires a deep reform in all spheres of social life according to the EU standards. It is very important for Moldova to take the experience of the European member - states which were the part of the socialist camp in the past. Republic of Bulgaria is a successful example of the territorial - administrative reform in the spirit of the European requirements. The purpose of the study is to investigate the achievements of Bulgaria on the boundary delimitation in accordance with accepted standards in the EU. There are analyzed the decentralization processes of the local public administration, of the territorial consolidation of the local collectivities. It was generalized the acquired experience of the Republic of Bulgaria and were made the useful suggestions for their implementation in reforming the territorial - administrative delimitation of the Republic of Moldova.